The incredible shrinking suit - Strathearn, Chris; Hachette (Firm) (New York Little, Brown and Company, 2015)
After stealing a top secret shrink-suit, Scott Lang sets out to test the suit's capabilites and finds himself the size of ant which comes with its own challenges as he faces the neighbors dog, a vaccuum, and a shower.
At head of title: Marvel Ant-Man.
"Inspired by the film!"--Cover.
"Inspired by Marvel's Ant-Man. Based on the screenplay by Adam McKay & Paul Rudd. Story by Edgar Wright & Joe Cornish. Produced by Kevin Feige. Directed by Peyron Reed."
104781
Keywords: Size -- Juvenile fiction; Adventure stories; Superheroes -- Juvenile fiction; Size -- Fiction; Adventure and adventurers -- Fiction